2019
DOI: 10.2196/12587
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of a Mobile Health Solution for Postpartum Pelvic Floor Muscle Training: Pilot Randomized Controlled Feasibility Study

Abstract: Background The postpartum period is a vulnerable time for the pelvic floor. Early implementation of pelvic floor muscle exercises, appropriately termed as pelvic floor muscle training (PFMT), in the postpartum period has been advocated because of its established effectiveness. The popularity of mobile health (mHealth) devices highlights their perceived utility. The effectiveness of various mHealth technologies with claims to support pelvic floor health and fitness is yet to be substantiated throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 55 publications
0
42
0
1
Order By: Relevance
“…Of the 10 studies, 3 (30%) investigated the effectiveness of stand-alone apps [ 35 , 39 , 42 ], and 1 (10%) used an audio guidance app [ 43 ]. Another study (1/10, 10%) evaluated an app that uses Bluetooth technology to link data from biofeedback [ 36 ]. Of the 8 apps, except for 1 (13%) [ 40 ], all mHealth apps (n=7, 88%) provided asynchronous PFMT—there was no live communication with a trainer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 10 studies, 3 (30%) investigated the effectiveness of stand-alone apps [ 35 , 39 , 42 ], and 1 (10%) used an audio guidance app [ 43 ]. Another study (1/10, 10%) evaluated an app that uses Bluetooth technology to link data from biofeedback [ 36 ]. Of the 8 apps, except for 1 (13%) [ 40 ], all mHealth apps (n=7, 88%) provided asynchronous PFMT—there was no live communication with a trainer.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the iBall app was unable to demonstrate improved adherence owing to technical difficulties and discomfort faced by study participants because of the external device [ 36 ]. Although the iBall app had various sophisticated persuasive features such as an interesting user interface, Bluetooth connection with an external device, and gamification, these features were not sufficient to overcome the problems with user acceptance of the external device.…”
Section: Resultsmentioning
confidence: 99%
“…Selected studies were published between 2013 and 2021, of which 10 studies [ 32 36 , 41 , 43 , 44 , 47 , 48 ] were written in English and the remaining were written in Chinese, originating from 7 countries, including China (15 studies) [ 37 – 40 , 42 , 45 – 47 , 49 – 55 ], Brazil (2 studies) [ 32 , 34 ], Sweden (2 studies) [ 33 , 44 ], the US (2 studies) [ 43 , 48 ], the UK (1 study) [ 36 ], Canada (1 study) [ 35 ], and The Netherlands (1 study) [ 41 ]. The 24 studies included 3691 women who were diagnosed with pelvic floor disorders or at risk of PFD, among whom 1862 were allocated to the eHealth group and 1829 to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The 24 studies included 3691 women who were diagnosed with pelvic floor disorders or at risk of PFD, among whom 1862 were allocated to the eHealth group and 1829 to the control group. Among all the studies, various eHealth technologies were observed, including: mobile phone or tablet applications (7 studies) [ 32 , 33 , 36 , 38 , 40 , 41 , 45 ], internet (9 studies) [ 37 , 39 , 42 , 44 , 46 , 49 – 51 , 55 ], telemetry device (1 study) [ 34 ], video (2 studies) [ 43 , 54 ], audio (1 study) [ 47 ], telephone (2 studies) [ 52 , 53 ], and mixed technologies, where more than one eHealth modality was reported (2 studies combined telemetry devices with applications) [ 35 , 48 ]. The characteristics of eligible studies are displayed in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Am Beispiel Urolithiasis lässt sich zudem zeigen, dass Smartphone-Applikationen sogar teilweise schädlich sein können, wenn sie nicht medizinisch korrekten Inhalt gewährleisten [ 24 ]. Daneben wurden an der Schnittstelle zur Urogynäkologie in der Inkontinenzbehandlung der Frau zahlreiche digitale Behandlungsformen von Beckenbodentraining erprobt [ 25 ], wobei in hochmotivierten Probanden bessere Behandlungserfolge erzielt werden [ 26 ]. Perioperativ kann Aktivitätstracking eingesetzt werden, um Aktivitätsniveaus beispielsweise für Patienten zu erfassen, die sich einer Prostatektomie unterziehen [ 27 ].…”
Section: „Digital Health“ In Der Urologieunclassified